FDI and economic transformation in Sub-saharan Africa: paper prepared for the Midlands State University 1st International Research Conference: Driving Socio-Economic Development through Value Addition and Sustainable use of Resources held at Elephant Hills Resort, Victoria Falls, Zimbabwe 14-16 July 2015 - Mufudza, Voronica; Tambudzai, Zachary; Kalotay, Kalman (Midlands State University, 2016)
Foreign direct investment (FDI) is widely considered one essential element for achieving sustainable development. This paper seeks to establish how much of the FDI activities in Sub-Saharan Africa (SSA) have translated into economic benefit for the host countries. It extends the analysis of aggregate FDI-growth relationships to intra and inter-sector spill-over effects, thereby reconciling the often inconclusive evidence on the growth impact of FDI in SSA. An interrogation of the figures in an econometric estimation of the FDI-growth relationship reveals that while FDI may seem like a key phenomenon of the century when measured by the rate it has been growing in Africa, this international interest in the region is yet to be translated into generation of livelihood and growth opportunities for recipient countries. The findings are important in light of Zimbabwe’s current economic woes characterized by low FDI inflows. FDI attraction has been proffered as a panacea to the current recession but the question is its sustainability given the turbulent political and socio-economic environment.